The Analysis of Category Shift in Surah Ibrahim Verses 1-52 - Nurhayati S. (International Journal of English and Applied Linguistics (IJEAL), 2021)
Abstracts The translation from the source language into the target language cannot be exact equivalents as both languages are widely different in structure and cultural background. One of the rules in doing the translation is about the shift. This study was carried out to examine the category shift of the translation of  Surah Ibrahim verses 1-52. The data collection uses the source text (English text) and targets text (Indonesian text) from the Quran. The step of this research is to scan all English words (ST) and their Indonesian translation (TT) instead of, according to Catford's theory (1965: 76) ) Identify category transfers. These transfers are divided into structural transfers, class transfers, unit transfers, and intra-system transfers. The dominant category shift results are Unit Shift (46, 71%); Structure Shift with 16,78%; Intra System Shift with the percentage of 16,45%. It was found that several combinations of the category shifts were Unit Shift + Intra System Shift, Unit Shift + Class Shift, Unit Shift + Structure Shift, and Intra System Shift + Structure Shift with a low percentage. The findings of this study were not in line with the writer's previous research for the number of the kinds of the category shift and its domination. It is expected that this study can be one of the references of another related research.